2003
DOI: 10.1177/01708406030247002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Workplace Envy Through Narrative Fiction

Abstract: In this article, we explore the social construction of workplace envy through an analysis of its portrayal in a fictional narrative. Based on our examination of three excerpts from Richard Russo's novel Straight Man, we argue that envy is socially constructed in prominent and revealing episodes within broader organizational narratives. We further show that envy both serves as a catalytic emotion that engenders action and sensemaking, and at the same time, acts as a mechanism that reproduces the moral and cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 49 publications
1
62
0
7
Order By: Relevance
“…It is thus not surprising that envy remains an unexamined issue in the field of stakeholder relationships and in the small-business context, in particular. Patient et al (2003) concluded that feelings of envy are often viewed as negative and disgraceful. Positive emotions are perhaps more easily accepted as the foci of research.…”
Section: Envy In Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is thus not surprising that envy remains an unexamined issue in the field of stakeholder relationships and in the small-business context, in particular. Patient et al (2003) concluded that feelings of envy are often viewed as negative and disgraceful. Positive emotions are perhaps more easily accepted as the foci of research.…”
Section: Envy In Relationshipsmentioning
confidence: 99%
“…From a non-malicious perspective, benign envy indicates the possibility that envy can motivate people to excel by raising themselves instead of bringing others down (Tai et al 2012). Benign envy can work as an incentive for activity that aims to improve one's status and performance (Duffy et al, 2008;Patient et al, 2003;Tai et al 2012). Envy can thus serve as a catalytic emotion that engenders action and sensemaking.…”
Section: Envy In Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…The third one is social constructivism approach which is used in order to reveal envy in an organizational setting. The only study based on this approach was made by Patient, Lawrence and Maitlis (2003). These researchers attempted to analyze envy in work environment through discourse analysis method by using three passages from Richard Russo's novel "Straight Man" which was published in 1997.…”
Section: Relational Studies That Examine Envy In Organizationsmentioning
confidence: 99%